Mary Berry's Complete Cookbook - Berry, Mary (London Dorling Kindersley Ltd., 2013)
Features over 1,000 tried and tested recipes for every occasion from firm family favourites to more adventurous dinner party dishes. As well as traditional classics and the author's all-time favourites, this title offers a selection of healthy low-fat dishes and new ideas to give you inspiration every time.
Include Color Illustrations and Index.
Keywords: Cooking